Brain responses to negated and affirmative meanings in the auditory modality - Farshchi, Sara; Andersson, Annika; van de Weijer, Joost; Paradis, Carita (Frontiers in Human Neuroscience, 2023)
Negation is frequently used in natural language, yet relatively little is known about its processing. More importantly, what is known regarding the neurophysiological processing of negation is mostly based on results of studies using written stimuli (the word-by-word paradigm). While the results of these studies have suggested processing costs in connection to negation (increased negativities in brain responses), it is difficult to know how this translates into processing of spoken language. We therefore developed an auditory paradigm based on a previous visual study (Farshchi et al., 2021) investigating processing of affirmatives, sentential negation (not), and prefixal negation (un-). The findings of processing costs were replicated but differed in the details. Importantly, the pattern of ERP effects suggested less effortful processing for auditorily presented negated forms (restricted to increased anterior and posterior positivities) in comparison to visually presented negated forms. We suggest that the natural flow of spoken language reduces variability in processing and therefore results in clearer ERP patterns.